2021
DOI: 10.1038/s41598-021-87343-3
|View full text |Cite
|
Sign up to set email alerts
|

North American boreal forests are a large carbon source due to wildfires from 1986 to 2016

Abstract: Wildfires are a major disturbance to forest carbon (C) balance through both immediate combustion emissions and post-fire ecosystem dynamics. Here we used a process-based biogeochemistry model, the Terrestrial Ecosystem Model (TEM), to simulate C budget in Alaska and Canada during 1986–2016, as impacted by fire disturbances. We extracted the data of difference Normalized Burn Ratio (dNBR) for fires from Landsat TM/ETM imagery and estimated the proportion of vegetation and soil C combustion. We observed that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 89 publications
(128 reference statements)
4
33
1
Order By: Relevance
“…In line with the general recognition of North American forests acting as a carbon sink (Pan et al, 2011), we observed either a positive or neutral net NABP in the Northern American Boreal and Temperate regions. Negative NABP estimates were also observed locally that could be associated with fire regimes (Zhao et al, 2021).…”
Section: Global Patterns Of Forest Carbon Changesmentioning
confidence: 95%
“…In line with the general recognition of North American forests acting as a carbon sink (Pan et al, 2011), we observed either a positive or neutral net NABP in the Northern American Boreal and Temperate regions. Negative NABP estimates were also observed locally that could be associated with fire regimes (Zhao et al, 2021).…”
Section: Global Patterns Of Forest Carbon Changesmentioning
confidence: 95%
“…Nutrients, trace elements, and pollutants are also released during soil warming, affecting plant growth, microbial activity, and human health (Keuper et al, 2012;Chen et al, 2018;Hewitt et al, 2018;Carey et al, 2019;UNEP, 2019;Mu et al, 2020b;Yang et al, 2021;Basu et al, 2022). While increased nutrient availability and CO 2 fertilization have long been predicted to enhance plant uptake of atmospheric CO 2 , observed trends of primary productivity in the permafrost domain have been mixed because of vegetation shifts, droughts, and other disturbances (Forbes et al, 2010;Hayes et al, 2011;Abbott et al, 2016b;McGuire et al, 2018;Rocha et al, 2018;Myers-Smith et al, 2020;Bruhwiler et al, 2021;Mack et al, 2021;Zhao et al, 2021;Vitali et al, 2022).…”
Section: Unstable Footing: Terrestrial Permafrost Degradationmentioning
confidence: 99%
“…Forest fires are fast-spreading, sudden and difficult to control. They cause massive forest damage and severely affect the composition of ecosystems, leading to a dramatic reduction in biomass and drastic changes in the landscape and the global carbon cycle ( Xaud, da Martins & Dos Santos, 2013 ; De Faria et al, 2017 ; Liu, Ballantyne & Cooper, 2019 ; Zhao et al, 2021b , 2021a ). In recent years, global warming and frequent human production activities have increased forest fires worldwide ( Hall et al, 2016 ; Forkel et al, 2019 ; Vargas-Cuentas & Roman-Gonzalez, 2021 ).…”
Section: Introductionmentioning
confidence: 99%